Credible Communication and Cooperation: Experimental Evidence from Multi-stage Games - Ola Andersson; Erik Wengström (Research Institute of Industrial Economics (IFN), 2011)
It is well known that communication often serves as a facilitator for cooperation in static games. Yet, communication can serve entirely different purposes in dynamic settings as communication during the game may work as a means for renegotiation, potentially undermining the credibility of cooperative strategies. To explore this issue, this paper experimentally investigates cooperation and non-binding communication in a two-stage game. More specifically, two treatments are considered: one with only pre-play communication and one where subjects can also communicate intra-play between the stages of the game. The results highlight a nontrivial difference concerning the effects of pre-play communication between the two treatments. Pre-play communication only has a significant impact on cooperation when no intra-play communication is possible. The results suggest that the credibility of pre-play messages may depend crucially on future communication opportunities.
Keywords: C72; C92; 330; Communication; Cooperation; Renegotiation; Experiments; Kommunikation; Verhandlungen; Kooperation; Dynamisches Spiel; Nichtkooperatives Spiel